2012
DOI: 10.5588/ijtld.11.0733
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis among adults starting antiretroviral therapy in South Africa: the need for routine case finding

Abstract: Background:We investigated the prevalence of, and evaluated screening modalities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 24 publications
2
37
0
1
Order By: Relevance
“…The review included four studies conducted during the ART era and, though overall ART coverage was not included, TB prevalence in these four studies was equal to or greater than in studies conducted prior to ART rollout, suggesting that individuals are initiating ART too late or are not linked to treatment at all. Studies conducted in clinics in South Africa have previously highlighted the large burden of undiagnosed TB among the ambulatory HIV-positive population [30,31], but investigation for TB is largely based on reporting respiratory symptoms, using sputum-based diagnostic tests [32,33]. A recent study conducted in Cape Town found that, of 139 HIV-positive individuals diagnosed with TB during admission to hospital (median CD4 count 80 cells/μL; 35% on ART for a median 1.3 years), 115 (83%) had at least one non-respiratory sample that was positive on testing with Xpert® MTB/RIF, or culture positive for M .…”
Section: Discussionmentioning
confidence: 99%
“…The review included four studies conducted during the ART era and, though overall ART coverage was not included, TB prevalence in these four studies was equal to or greater than in studies conducted prior to ART rollout, suggesting that individuals are initiating ART too late or are not linked to treatment at all. Studies conducted in clinics in South Africa have previously highlighted the large burden of undiagnosed TB among the ambulatory HIV-positive population [30,31], but investigation for TB is largely based on reporting respiratory symptoms, using sputum-based diagnostic tests [32,33]. A recent study conducted in Cape Town found that, of 139 HIV-positive individuals diagnosed with TB during admission to hospital (median CD4 count 80 cells/μL; 35% on ART for a median 1.3 years), 115 (83%) had at least one non-respiratory sample that was positive on testing with Xpert® MTB/RIF, or culture positive for M .…”
Section: Discussionmentioning
confidence: 99%
“…In developing countries, the diagnosis of pulmonary TB is heavily dependent on AFB sputum smear microscopy, which has low sensitivity among PLHIV [14], who often present extra pulmonary or sputum smear-negative pulmonary TB, resulting in late diagnosis [15] and therefore either delayed or no treatment [16]. This has led to the suggestion that empirical treatment of tuberculosis (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organisation (WHO) estimates that approximately 20e40% of the world's population are affected, with 8e9 million new cases of active disease being reported every year [9e16]. TB is ultimately responsible for most deaths among patients infected with the human immunodeficiency virus (HIV) [8,17,18,19,20].…”
Section: Introduction Q1mentioning
confidence: 99%